Pendekatan Spasial dalam Penentuan Prioritas Area Irigasi pada Musim Kering - Mouli De Rizka Dewantoro (Balai Teknik Irigasi, 2013)
Rice paddy fields in the northern part of West Java is one of the national granary. Sources water for irrigation of paddy field in the northern part of West Java largely sourced from the Citarum River, into the Jatiluhur reservoir and channeled into irrigation canals irrigated area northern of West Java. Management of water distribution should consider priority of irrigated land in order to obtain maximum results. Geographic Information Systems (GIS) can serve as a method that can be used to process data based on spatial references. GIS and disaster approaches to be one that can be an alternative approach to the prioritization of irrigation on paddy fields. The dry season in Indonesia often results in some areas of drought disasters are no exception to the paddy fields. The drought also resulted in crop failures that make reduced production of rice in Indonesia. Approach and drought factors may be one factor considered in the prioritization of irrigation so as to maximize the irrigation system. The results has obtained from this research is priority areas of irrigation map in the northern region of West Java. Result of this research is show that the first priority area for irrigation about 9.385,87 ha.